Real‐life applicability of the Euroarray dermatomycosis kit in the diagnosis of onychomycosis. Issue 3 (10th January 2022) - Trave, Ilaria; Cozzani, Emanuele; Canepa, Paola; Verdiani, Simonetta; Parodi, Aurora
Abstract: Background: Traditionally, KOH microscopy and fungal culture are the two preferred tests as gold standard for diagnosis of onychomycosis. Recently, other diagnostic methods have been developed to improve the microbiological diagnosis. The EUROArray dermatomycosis kit is a PCR‐based microarray test system for the detection and direct identification of species that are most frequently involved in skin and nail infections. Objectives: Our primary aim was to evaluate the real‐life applicability of the EUROArray dermatomycosis kit in the diagnosis of onychomycoses. In addition, we compared the aetiology of onychomycoses found in our patients with those described in the literature. Patients/Methods: We prospectively studied consecutive 100 patients with suspected onychomycoses. Samples of suspect toenails were taken as part of routine medical management. Nail specimens were evaluated by means of three diagnostic methods: KOH preparation, culture and EUROArray dermatomycosis kit. Results: Onychomycosis was diagnosed in 47/100 patients who proved positive on at least one reference diagnostic test and in 49/100 patients who proved positive on PCR. The combination of microscopy and PCR had better sensitivity than microscopy ( p = .0397), fungal culture ( p = .0061) and PCR alone ( p = .0117). Moulds were more frequently positive in culture than in PCR ( p = .033). Dermatophytes proved positive more frequent than moulds and yeasts in both culture and PCR; in particular, Trichophyton interdigitale was the most frequent pathogen. Conclusions: In conclusion, introducing EUROArray dermatomycosis kit into the diagnostic algorithm of onychomycosis increases the sensitivity of direct microscopy and yields more rapid results than culture.